Effects of iron chelation therapy on the clinical course of aceruloplasminemia: an analysis of aggregated case reports - Vroegindeweij, Lena H. P.; Boon, Agnita J. W.; Wilson, J. H. Paul; Langendonk, Janneke G. (Orphanet journal of rare diseases, 2020)
Background Aceruloplasminemia is a rare genetic iron overload disorder, characterized by progressive neurological manifestations. The effects of iron chelation on neurological outcomes have only been described in case studies, and are inconsistent. Aggregated case reports were analyzed to help delineate the disease-modifying potential of treatment. Methods Data on clinical manifestations, treatment and neurological outcomes of treatment were collected from three neurologically symptomatic Dutch patients, who received deferiprone with phlebotomy as a new therapeutic approach, and combined with other published cases. Neurological outcomes of treatment were compared between patients starting treatment when neurologically symptomatic and patients without neurological manifestations. Results Therapeutic approaches for aceruloplasminemia have been described in 48 patients worldwide, including our three patients. Initiation of treatment in a presymptomatic stage of the disease delayed the estimated onset of neurological manifestations by 10 years (median age 61 years, SE 5.0 vs. median age 51 years, SE 0.6, p = 0.001). Although in 11/20 neurologically symptomatic patients neurological manifestations remained stable or improved during treatment, these patients were treated significantly shorter than patients who deteriorated neurologically (median 6 months vs. median 43 months, p = 0.016). Combined iron chelation therapy with deferiprone and phlebotomy for up to 34 months could be safely performed in our patients without symptomatic anemia (2/3), but did not prevent further neurological deterioration. Conclusions Early initiation of iron chelation therapy seems to postpone the onset of neurological manifestations in aceruloplasminemia. Publication bias and significant differences in duration of treatment should be considered when interpreting reported treatment outcomes in neurologically symptomatic patients. Based on theoretical grounds and the observed long-term safety and tolerability in our study, we recommend iron chelation therapy with deferiprone in combination with phlebotomy for aceruloplasminemia patients without symptomatic anemia.